Influence of phosphate dosing on biofilms development on lead in chlorinated drinking water bioreactors - Del Olmo, Gonzalo; Ahmad, Arslan; Jensen, Henriette; Karunakaran, Esther; Rosales, Esther; Calero Preciado, Carolina; Gaskin, Paul; Douterelo, Isabel (NPJ biofilms and microbiomes, 2020)
Phosphate dosing is used by water utilities to prevent plumbosolvency in water supply networks. However, there is a lack of knowledge regarding biofilm formation on lead and plastic materials when phosphate concentrations are modified in drinking water systems. In this study, biofilms were grown over lead coupons and PVC tubes in bioreactors supplied with local drinking water treated to provide different phosphate doses (below 1, 1 and 2 mg/L) over a period of 28 days. A range of commercial iron pellets (GEH104 and WARP) were tested aiming to maintain phosphate levels below the average 1 mg/L found in drinking water. Changes in biofilm community structure in response to three different phosphate treatments were characterised by Illumina sequencing of the 16S rRNA gene for bacteria and the ITS2 gene for fungi. Scanning electron microscopy was used to visualise physical differences in biofilm development in two types of materials, lead and PVC. The experimental results from the kinetics of phosphate absorption showed that the GEH104 pellets were the best option to, in the long term, reduce phosphate levels while preventing undesirable turbidity increases in drinking water. Phosphate-enrichment promoted a reduction of bacterial diversity but increased that of fungi in biofilms. Overall, higher phosphate levels selected for microorganisms with enhanced capabilities related to phosphorus metabolism and heavy metal resistance. This research brings new insights regarding the influence of different phosphate concentrations on mixed-species biofilms formation and drinking water quality, which are relevant to inform best management practices in drinking water treatment.